Investigating the effect of magnetic dipole–dipole interaction on magnetic particle spectroscopy: implications for magnetic nanoparticle-based bioassays and magnetic particle imaging. (17th June 2019) - Wu, Kai; Su, Diqing; Saha, Renata; Liu, Jinming; Wang, Jian-Ping
Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs), with comparable size to biomolecules (such as proteins, nucleic acids, etc) and unique magnetic properties, good biocompatibility, low toxicity, potent catalytic behavior, are promising candidates for many biomedical applications. There is one property present in most SPION systems, yet it has not been fully exploited, which is the dipole–dipole interaction (also called dipolar interaction) between the SPIONs. It is known that the magnetic dynamics of an ensemble of SPIONs are substantially influenced by the dipolar interactions. However, the exact way it affects the performance of magnetic particle-based bioassays and magnetic particle imaging (MPI) is still an open question. The purpose of this paper is to give a partial answer to this question. This is accomplished by numerical simulations on the dipolar interactions between two nearby SPIONs and experimental measurements on an ensemble of SPIONs using our lab-based magnetic particle spectroscopy (MPS) system.